2022
DOI: 10.1101/2022.02.06.479316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stability Criterion for the Assembly of Hybrid Lipid-Polymer-Nucleic Acid Nanoparticles

Abstract: Hybrid lipid-polymer-nucleic acid nanoparticles (LPNPs) provide a range of delivery strategies for nonviral gene therapy. However, due to several pairwise interactions between their components, these formulations are difficult to predict and characterize. Here, we employed, for the first time, a novel methodology based on fluorescence cross correlation spectroscopy (FCCS) to directly quantify the extent of association between polycation-DNA cores (polyplexes) and cationic liposome shells. This leads to a rapid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…This methodology promises to become a powerful guide to the development of similar formulations and accelerate research and innovation in mRNA vaccine and cancer vaccine development. As an example, in a recent development as a follow-up of this research, we report on the discovery of a new stability criterion for the preparation of stable hybrid lipid-polymer-nucleic acid nanoparticles [3].…”
Section: Discussionmentioning
confidence: 99%
“…This methodology promises to become a powerful guide to the development of similar formulations and accelerate research and innovation in mRNA vaccine and cancer vaccine development. As an example, in a recent development as a follow-up of this research, we report on the discovery of a new stability criterion for the preparation of stable hybrid lipid-polymer-nucleic acid nanoparticles [3].…”
Section: Discussionmentioning
confidence: 99%
“…16 Class II and class IV (low solubility) categories include many of the newly synthesized drug molecules, 16,17 denoting that the solubility or rate of dissolving in the gastrointestinal tract are the pronounced constrains for their absorption. 18 Various commonly used systems to increase bioavailability of these drug candidates include nanoparticle-based formulations, [19][20][21][22] lipid and polymer-based drug delivery systems, [23][24][25][26][27][28] and pro-drugs. [29][30][31] Winzen et al recently demonstrated that PDMS-b-PMOXA/ cholesterol hybrid vesicles show a drastically increased bending stiffness compared to pure PDMS-b-PMOXA polymersomes and PDMS-b-PMOXA/DMPC (1,2-dimyristoyl-sn-glycero-3-phosphocholine) vesicles which was attributed to a higher packing density due to the presence of cholesterol in hybrid vesicle membranes.…”
Section: Introductionmentioning
confidence: 99%
“…16 Class II and class IV (low solubility) categories include many of the newly synthesized drug molecules, 16,17 denoting that the solubility or rate of dissolving in the gastrointestinal tract are the pronounced constrains for their absorption. 18 Various commonly used systems to increase bioavailability of these drug candidates include nanoparticle-based formulations, 19–22 lipid and polymer-based drug delivery systems, 23–28 and pro-drugs. 29–31…”
Section: Introductionmentioning
confidence: 99%